Legal Protection of Minors Whose Land Certificates are Used as Collateral for Debts - Hidayat, Maxe; Rokhim, Abdul; Sunardi, Sunardi (JURNAL USM LAW REVIEW, 2025)
This study aims to analyze the legal consequences of minors' land certificates used as debt collateral by their biological mothers and legal protection for minors whose land rights are used as debt collateral by their biological mothers. The research method used is normative juridical using statutory, conceptual, and case approaches. Minors (minderjarig) according to the law are not capable of performing legal acts independently, including in terms of making their land rights as forest collateral. Legal actions of minors whose fathers die can be represented by their biological mothers who act as guardians based on court decisions. The urgency of this research is to provide a description and analysis of guardians who replace their parents to replace minors to carry out legal processes by analyzing the cases raised. The case raised is the novelty of the results of this research analysis. The results of this study indicate that the legal consequences of a minor's land certificate used as debt collateral by his biological mother without going through the determination of the guardian and the power of attorney to make the minor's land rights from the court are null and void (nietig van rechtswege). The law (Article 393 of the Civil Code) has provided preventive legal protection against minors whose land titles are used as debt collateral by their biological mothers if this is done without the appointment of a guardian and power of attorney from the court. The minor's biological mother in her position as guardian is only authorized to make the certificate of land title on the basis of absolute necessity or clearly beneficial to the minor after hearing or legally summoning the child's immediate family or blood relatives and the supervisory guardian.